2020
DOI: 10.3390/w12061638
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Physicochemical Properties of Water Treated under Methane with Low-Temperature Glow Plasma of Low Frequency

Abstract: Our former studies delivered a strong evidence that water indirectly treated with low-temperature, low-pressure glow plasma of low frequency (GP) changed its structure depending on the atmosphere in which such treatment was performed (air, ammonia, and nitrogen) and on the time of the treatment (0 to 120 min). In every case, water of different physicochemical characteristics and interesting biological functions was produced. Therefore, the relevant studies were extended to treating deionized water with GP unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Water treated for the same time with LGPG under nitrogen as described by Chwastowski et al, [7] produced LPGPN. LPGPC [13], LPGPO [9] and LPGPM [12] were prepared following the procedures described in the indicated references. LPGP of 38 • C was generated at 5 × 10 −3 mbar, 800 V, 50 mA and 10 KHz frequency in a plasmothrone patented by Oszczęda et al [1,10].…”
Section: Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Water treated for the same time with LGPG under nitrogen as described by Chwastowski et al, [7] produced LPGPN. LPGPC [13], LPGPO [9] and LPGPM [12] were prepared following the procedures described in the indicated references. LPGP of 38 • C was generated at 5 × 10 −3 mbar, 800 V, 50 mA and 10 KHz frequency in a plasmothrone patented by Oszczęda et al [1,10].…”
Section: Watermentioning
confidence: 99%
“…Following the invention of LPGP and the construction of a generator suitable for the treatment of water [1,7,10], a series of papers were published on the specific physical and physicochemical properties of water treated with LPGP in the air (LPGPA) [8], under all oxygen-free nitrogen (LPGPN) [7], ammonia (LPGPAM) [11], methane (LPGPM) [12], carbon dioxide (LPGPC) [13], and molecular oxygen (LPGPO) [9]. Based on these various studies, the functional properties of such treated water could be applied to agriculture and various branches of industry, as well as human and animal prophylaxis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Following the invention of LPGP and a generator suitable for treatment of water [37,38], a number of papers were published. They dealt with specific physical and physicochemical properties of water treated with LPGP in atmospheric conditions (LPGPA) [35], but also under oxygenfree nitrogen (LPGPN) [38], ammonia (LPGPAM) [39], methane (LPGPM) [40], carbon dioxide (LPGPC) [34], and molecular oxygen (LPGPO) [38].…”
Section: Introductionmentioning
confidence: 99%
“…These properties depended, among others, on the time of exposure of the water to GP and the atmosphere under which the GP treatment was performed. Thus far, the effect of the air [6], oxygen-free nitrogen [7], carbon dioxide [8], methane [9] and oxygen [10] upon results of the GP treatment was published. In the course of our studies, we found that the energy of applied GP never broke valence bonds and could not initiate any chemical reaction.…”
Section: Introductionmentioning
confidence: 99%